2021
DOI: 10.3390/app11041446
|View full text |Cite
|
Sign up to set email alerts
|

More than XRF Mapping: STEAM (Statistically Tailored Elemental Angle Mapper) a Pioneering Analysis Protocol for Pigment Studies

Abstract: Among the possible variants of X-Ray Fluorescence (XRF), applications exploiting scanning Macro-XRF (MA-XRF) are lately widespread as they allow the visualization of the element distribution maintaining a non-destructive approach. The surface is scanned with a focused or collimated X-ray beam of millimeters or less: analyzing the emitted fluorescence radiation, also elements present below the surface contribute to the elemental distribution image obtained, due to the penetrative nature of X-rays. The importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Even if only some of the spectra could be attributed to recognisable pigments, by combining the elemental distribution data and SAM maps a mixture of materials could be identified that matched the description given by the artist in his “ Small Treatise on Pictorial Technique ” (De Chirico in Abscondita, 2019). The importance of the macroXRF spectrometry scanning technique in the investigation of historical paintings was highlighted by Orsilli et al , 93 who discussed its advantages and limitations and emphasised the challenges of handling the large data set and the inhomogeneity of the data itself. An impressive pioneering protocol called STEAM (Statistically Tailored Elemental Angle Mapper) was based on the SAM algorithm and combined macroXRF standard data with point XRF spectrometry data.…”
Section: Cultural Heritage Applicationsmentioning
confidence: 99%
“…Even if only some of the spectra could be attributed to recognisable pigments, by combining the elemental distribution data and SAM maps a mixture of materials could be identified that matched the description given by the artist in his “ Small Treatise on Pictorial Technique ” (De Chirico in Abscondita, 2019). The importance of the macroXRF spectrometry scanning technique in the investigation of historical paintings was highlighted by Orsilli et al , 93 who discussed its advantages and limitations and emphasised the challenges of handling the large data set and the inhomogeneity of the data itself. An impressive pioneering protocol called STEAM (Statistically Tailored Elemental Angle Mapper) was based on the SAM algorithm and combined macroXRF standard data with point XRF spectrometry data.…”
Section: Cultural Heritage Applicationsmentioning
confidence: 99%
“…Again on MA-XRF, the work by Orsilli and co-authors [7] summarizes the advantages and limitations of MA-XRF, here considered as an imaging technique. This allows a better synergy with other hyperspectral methods, or the combination with spot investigations.…”
Section: Review Of Issue Contentsmentioning
confidence: 99%
“…A third paper to report the use of macro-XRF for the analysis of pigments was presented by Orsilli et al 369 These authors combined macro-XRF with Statistically Tailored Elemental Angle Mapper for the analysis of a painting by Giotto. The paper is partially an overview (with 54 references) that discussed the relative merits and limitations of using macro-XRF.…”
Section: Cultural Heritagementioning
confidence: 99%